MENANAMKAN NILAI-NILAI HAK ASASI MANUSIA (HAM) DAN SYARI’AT ISLAM MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAM ACHIEVEMENT DIVISION) DI SEKOLAH - muhamad afandi (Jurusan PGMI FTIK IAIN Metro Lampung, 2015)
Planting of human rights values in primary schools is given according to the needs and level of development is intended to be the material easily understood, understood and interpreted by students. The goal is to determine the level of development of value investment implementation of human rights in schools, including obstacles and opportunities in implementing an effective learning model related to the planting of the values of human rights in school. Education should be conducted in an atmosphere of fair and democratic learning in instilling values social-value (togetherness), cultural (culture), plural (plurality), and spiritual (religious) to the students. STAD cooperative learning model is one type of cooperative learning model that can reduce negative values contradictory to the values of human rights and Islamic Shari’a in the learning process. Instead, this model is able to actualize the values of human rights and Islamic Shari’a in the learning process. By implementing cooperative learning model type STAD learning in primary schools, is expected to instill the values of human rights and Islamic Shari’a since an early age that will eventually give birth to a citizen who has insight and knowledge of basic rights or fundamental attached to himself and others as a gift of God that must be respected, protected, and protected by any individual, community or state in everyday life.